Reflex Epilepsy Induced by "Soroban", A Japanese Calculator - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
Three patients with reflex epilepsy and myoclonic jerks of the right arm and fingers precipitated by calculation using a Soroban are reported from the Department of Neuropsychiatry, Osaka University Medical School, Fukushima-ku, Osaka, Japan.